KEBERADAAN DAN DISTRIBUSl JENIS-JENIS Trichoderma DI HUTAN KAWASAN TAMAN NASIONAL GUNUNG HALIMUN - Nandang Suharna (Research Center for Biology-Indonesian Institute of Sciences, 2002)
A study was conducted m determine the occurrence and distribution of Trichoderma species in forest in Gunung Halimun National Park. Location for data ollection were Cikaniki (1.100 asl), Citalahab (1.100 asl.)and Gunung Botol (1.500 asl, 1.600 asl,and 1.700 asl).Isolation of Trichoderma were from non vegetation soils, rhizosphere soils and stumps of three dominating forest trees i.e.Allingia excelsa,Caslanopsis javanicti and Schimu wallichii.The isolation method used were soil plate (non vegetation soil,Rhizosphere soil), dilution plate (non vegetation soil.Rhizosphere soil) and surface sterilization (stump).Trichoderma viride recorded as the commonest fungus of its occurrence and the most widespread in non vegetation soil in all location studied. Other Trichoderma species encountered were T. longibrachialuin, T. virens T. koningii.T. hamaium. T. pseudokoningii and T. polysporum. While in rhizosphere soils of the three dominating trees Allingia excelsa. Schima wallichii. and Casianopsis javanica) located in Cikaniki, T. hamatum, was the commonest fungus of its occurrence. Another common was T. koningii. Other species were rarely encountered were T. longibrachialum, T. virens, T. pseudokoningii and T. polysporum, and T. fertile. In stumps of four trees in Cikaniki four species of Trichoderma were recorded of their occurrences. They were T. harzianum (Memecylon excelsum). T. koningii (S. wallichii), T. viride (A. excelsa, S. wallichii and C. javanica) and T. virens (A. excelsa and M. excelsum). It i> concluded that in forest of Gunung Halimun National Park, habitat influenced on the occurrence and distribution of Trichoderma species, but not for altitude. Trichoderma was high in diversity, dominant in occurrence and widespread in distribution.",